Changing landscape of hereditary breast and ovarian cancer germline genetic testing in Australia. Issue 10 (4th October 2018) - Petelin, Lara; James, Paul A.; Trainer, Alison H.
Abstract: Federal funding for germline genetic testing in hereditary breast and ovarian cancer (HBOC) was recently introduced. Germline testing for HBOC under Medicare Benefits Schedule items 73296/73297 can be requested by any specialist, whereas the previous state‐ and territory‐funded testing was limited to those operating within a familial cancer service. The impact of this decentralisation of HBOC testing on health and economic outcomes is uncertain, primarily as it has potential to significantly disrupt the clinical framework that generated the evidence used to justify clinical implementation of the Medicare Benefits Schedules.